Enhancing Computational Thinking Skills Through Physics-Based Worksheet in Linear Motion - Fajrul Falah; Dwi Sulisworo (Radiasi : Jurnal Berkala Pendidikan Fisika, 2023)
The physics knowledge consists of many concepts and principles that are generally very abstract. Learning activities should help students understand the concepts by performing a series of activities themself. One of the required thinking skills in the 21st century is Computational Thinking Skills. Computational Thinking is the thinking process required in formulating problems and solutions. This study aims to develop a valid student worksheet and describe the students' response to it. In this research, the development of Computational Thinking-based student worksheet was carried out to be used in Junior High School science learning. Validation was carried out by media experts and subject matter experts. The results from the media experts were a score of 10.65 with an average of 3.55 from a scale of 4.0. While the results from subject matter experts were a score of 3.80 from a scale of 4.0. It can be concluded that the student worksheet received good and reliable categories. The effectiveness test on four students showed an average score of 7.25 in active learning style; an average score of 16.5 in reflective learning style; an average score of 12 in theoretical learning style; and an average score of 12.25 in pragmatic learning style. From these scores, it can be concluded that the dominant learning style of the four students who acted as respondents after following learning using the student worksheet is reflective learning, where students who like to consider experiences and observe learning materials from different perspectives.